CO2 Removal from Biogas Using Carbon Nanotubes Mixed Matrix Membranes - Tutuk Djoko Kusworo; Ahmad Fauzi Ismail; , Budiyono; I Nyoman Widiasa; Seno Johari; , Sunarso (International Journal of Science and Engineering, 2010)
A new type of mixed matrix membrane consisting of polyethersulfone (PES) and carbon nanotubes (CNTs) is prepared for biogas purification application. PES mixed matrix membrane with and without modification of carbon nanotubes were prepared by a dry/wet phase inversion technique using a pneumatically membrane casting machine system. The modified carbon nanotubes were prepared by treating the carbon nanotubes with chemical modification using acid treatment to allow PES chains to be grafted on carbon nanotubes surface. The results from the FESEM, DSC and FTIR analysis confirmed that chemical modification on carbon nanotubes surface had taken place. Meanwhile, the nanogaps in the interface of polymer and carbon nanotubes were appeared in the PES mixed matrix membrane with unmodified of carbon nanotubes. The modified carbon nanotubes mixed matrix membrane increases the mechanical properties and the permeability of all gases. For PES-modified carbon nanotubes mixed matrix membrane the maximum selectivity achieved for CO2/CH4 is 23.54